REGROWTH AND YIELD Asystasia gangetica (L.) subsp. Micrantha FERTILIZED WITH NPK SUBSTITUTED COW BIOURINE - E. E., Simanjuntak; E. E., Simanjuntak; Roni, N.G.K.; Kusumawati, N.N.C. (Jurnal Peternakan Tropika; Vol 12 No 1 (2024): Vol. 12 No. 1 Tahun 2024; January - February, 2024)
This study aimed to determine regrowth and yield Asystasia gangetica (L.) subsp. Micrantha fertilized with NPK substituted cow biourine. The research was conducted at the Sading Greenhouse, Sading, Mengwi, Badung Regency. The study lasted for 3 months, using a completely randomized design (CDR). There were 8 treatment combination and each treatment was repeated three times, so there were 24 experimental units. The eight treatments were D1 : NPK 200 kg ha-1; D2 : Biourine 5.000 l ha-1 ; D3 : Biourine 7.500 l ha-1; D4 : Biourine 10.000 l ha-1; D5 : NPK 50 kg ha-1 + Biourine 5.000 l ha-1; D6 : NPK 50 kg ha-1 + Biourine 7.500 l ha-1 ; D7 : NPK 100 kg ha-1 + Biourine 5.000 l ha-1; D8 : NPK 100 kg ha-1 + Biourine 7.500 l ha-1. Variables measured in this experiment were growth, yield, and plant growth characteristic variables. The results showed that the substitution of NPK fertilizer with biourine on D4 increased the variables of plant height, total dry weight of forage, and leaf area, nevertheless number of leaves, branches, dry weight of leaves, dry weight of stems and ratio of dry weight of leaves to stems gave the same result with NPK fertilizer treatment on Asystasia gangetica. It is concluded that substitution of NPK fertilizer with cow biourine increase regrowth, yield of Asystasia gangetica (L.) subsp. Micrantha and the best result is biourine 10.000 l ha-1.